Photovoltaic-based single-ended primary-inductor converter with dual-fuzzy logic control-based maximum power point tracking - Ramalu, Tanaselan (2016)
Among renewable energy sources, solar energy used in photovoltaic (PV) system is the most favorite list in renewable energy researches today. Due to its maintenance free, ease of implementation and free of pollution, its demand increases rapidly in residential and industrial applications. However, PV cell appears to have low power efficiency in the range of 15-30% and its market price is still expensive; these factors are the main disadvantages. Due to its nonlinear characteristic, a control technique, known as maximum power point tracking (MPPT), is a must in PV system in order to make sure that the output power of PV system is always staying at maximum power point (MPP). In general, MPPT can be divided into conventional and artificial intelligent algorithms. The most popular conventional algorithms are perturb and observe (P&O) and incremental conductance (IC). Their main weakness is these algorithms always fail to track MPP and high oscillation occurs whenever the sunlight (irradiance) changes frequently. Among artificial intelligent algorithms used in MPPT are neural network, fuzzy logic control (FLC) and genetic algorithm. In this work, FLC was selected because it is easy to be implemented and does not require mathematical model in its design. Dc-dc converter is used in most PV systems where it is attached with PV together with MPPT to obtain the maximum power transfer. In this work, single-ended primaryinductor converter (SEPIC) is preferred due to the need to perform both boost and buck operations depending on the supplied duty cycle to the converter’s switch. SEPIC also has explicit advantage over buck-boost converter where the output voltage polarity in SEPIC is not inverted as output voltage polarity in the buck-boost converter. Dual FLC MPPT is proposed in this work to support both operations of SEPIC. The first FLC part is for lower duty cycle (buck) and the second FLC part is for higher duty cycle (boost). Meanwhile, to realize dual-operation of SEPIC, dual-load approach has been applied by selecting suitable load resistance, which could achieve MPP with specific irradiance and duty cycle. Simulation work has been done by using MATLAB/ Simulink software. The work scopes under simulation include the PV modelling, SEPIC configuration, designing dual FLC MPPT and also designing load switching controller. In hardware configuration, solar simulator is used instead of PV panel. To make sure that both loads have continuous supply of power, two DC supplies have been attached to respective loads with additional of two intermediate controllers which are designed to control the switching of DC supplies and SEPIC converter connections (from PV) to both loads. Based on both simulation and experimental works, the SEPIC with dual FLC MPPT has performed with much more stable, faster response time, less oscillation and less ripples output as compared to P&O algorithm. In addition, through its operation with dual loads, maximum power has been obtained at lower irradiance by using higher resistance load, and during high irradiance, lower resistance load is needed in order to achieve maximum power.